Remarkable variability in dyke features at the Vicuña Pampa Volcanic Complex, Southern Central Andes. (26th May 2017) - Guzmán, Silvina; Neri, Marco; Carniel, Roberto; Martí, Joan; Grosse, Pablo; Montero‐López, Carolina; Geyer, Adelina
Abstract: Dykes at the Vicuña Pampa Volcanic Complex, which are mostly basaltic (trachy)‐andesite and (trachy)‐andesite, are exposed at the base and along the walls of a large depression resulting from intense degradation. Dykes intruding stiff layers (lavas, plugs and necks) are thin, mostly dip >60° and have coherent textures, whereas dykes intruding more compliant materials (breccias and conglomerates) tend to be thicker, have lower dips and have coherent, brecciated or mixed textures (coherent and brecciated textural domains in a single or compound dyke). Single dykes with brecciated and mixed textures are only found intruding near‐surface units. Dykes with mixed textures always have sharp contacts between domains. Dykes with sinuous domain contacts and enclaves of one domain inside the other are interpreted as resulting from dyke arrest, partial cooling and reinjection of new magma. Dykes with straight domain contacts are considered to be compound dykes, with a new dyke intruding along the margins of an older, solidified one.